2021
DOI: 10.1097/yic.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic factors associated with early relapse in patients with schizophrenia: a naturalistic observation study

Abstract: Schizophrenia is a chronic psychiatric disorder progressing in relapses. Identification of many factors that may potentially increase the risk of relapse will be an important step in preventing relapses. The aim of this study was to determine the rate of early relapse in patients with schizophrenia and possible risk factors related to early relapse. The sample of this prospective study with the naturalistic observation design consisted of 308 patients with schizophrenia. The cutoff value for early relapse was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Thus, the higher the number of previous hospitalizations, the higher the likelihood of rehospitalization. This is an interesting finding consistent with the literature on people with schizophrenia, where the number of previous hospitalizations was a predictor of early relapse (Gündoğmuş et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the higher the number of previous hospitalizations, the higher the likelihood of rehospitalization. This is an interesting finding consistent with the literature on people with schizophrenia, where the number of previous hospitalizations was a predictor of early relapse (Gündoğmuş et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, any episode of relapse constitutes a neurotoxic insult [73]. Over the years, a growing number of studies, in which participants were treated with newer drugs, confirmed relapse rates of between 20 and 38%, with peaks of up to 45% when maintenance treatment was discontinued [34,74,75]. In this perspective, Clozapine, considered the most potent drug in many randomised, prospective head-to-head trials, could also be used as a first-line treatment, in order to prevent early relapses and initial therapeutic failures [18,76].…”
Section: Clozapine As First and Second Line Treatment For Schizophren...mentioning
confidence: 99%